Strategies for enhancing Arabic language skills using flashcards: Introducing animal names based on hijaiyah letters - Asa Syifa'ul Huznia; Aziz Muzakia; Fuad Dzaky Al-Asyrof (Journal of Professional Teacher Education, 2025)
This study aims to examine the effectiveness of flashcards as an instructional strategy for enhancing Arabic vocabulary acquisition among children aged 5 to 12 years. The focus is on introducing animal names categorized according to hijaiyah letters. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. A total of 45 participants were involved in a three-week intervention using flashcards that integrated visual images, Arabic script, and phonetic transliteration. Data were collected through pretests and posttests and analyzed using a paired samples t-test. The findings revealed a significant improvement in students’ vocabulary mastery, as indicated by higher posttest scores compared to pretest results (p < 0.001) with a large effect size, demonstrating strong practical significance. In addition, observational data showed increased student engagement, confidence, and participation during the learning process. The study concludes that flashcards are an effective and accessible tool for improving basic Arabic vocabulary and supporting early language development. This instructional strategy is particularly relevant for early childhood education and learning environments with limited resources, as it offers a practical, low-cost, and engaging approach to Arabic language instruction.